ANALYSIS OF FACTORS AFFECTING VARYING MAXIMUM RANGE ABILITY FOR UNMANNED AERIAL VEHICLE - Kharchenko, Volodymyr; Plakhotniuk, Ievgen (Proceedings of National Aviation University, 2013)
We consider the importance of rejecting the controls for a particular unmanned aircraft in a hospital flight. It is shown how the balancing properties unmanned aircraft affect the flight range.